2020
DOI: 10.1111/jfb.14514
|View full text |Cite
|
Sign up to set email alerts
|

A review of the genus Strophidon (Anguilliformes: Muraenidae), with description of a new species

Abstract: Strophidon McClelland is a muraenid genus with characteristic appearance of a very elongated body, a large mouth cleft and anteriorly placed eyes. The nomenclature and taxonomic history of species within Strophidon are contentious and its members are easily misidentified. In the present study, species of the genus Strophidon are revised based on morphological and molecular data, and five species are considered valid, including S. dawydoffi Prokofiev, S. dorsalis (Seale), S. sathete (Hamilton), S. ui Tanaka and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…The results are largely similar to previous studies based on mitochondrial COI fragments, 12S and 16S rRNA genes (Tang and Fielitz 2013 ; Huang et al. 2020 ). Taken together, the newly sequenced mitochondrial genome of S. sathete characterized here should contribute to a better understanding of phylogenetic relationships of species in the family Muraenidae, and molecular identification, population genetic and evolutionary biological studies of the slender giant moray.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The results are largely similar to previous studies based on mitochondrial COI fragments, 12S and 16S rRNA genes (Tang and Fielitz 2013 ; Huang et al. 2020 ). Taken together, the newly sequenced mitochondrial genome of S. sathete characterized here should contribute to a better understanding of phylogenetic relationships of species in the family Muraenidae, and molecular identification, population genetic and evolutionary biological studies of the slender giant moray.…”
supporting
confidence: 91%
“…The phylogenetic tree (Figure 1) showed that S. sathete was first clustered with Rhinomuraena quaesita and Gymnothorax minor, which further elucidate the phylogenetic and taxonomic position of the genus Strophidon in the family Muraenidae. The results are largely similar to previous studies based on mitochondrial COI fragments, 12S and 16S rRNA genes (Tang and Fielitz 2013;Huang et al 2020). Taken together, the newly sequenced mitochondrial genome of S. sathete characterized here should contribute to a better understanding of phylogenetic relationships of species in the family Muraenidae, and molecular identification, population genetic and evolutionary biological studies of the slender giant moray.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The misidentifications that occur during the process of developing the DNA barcode library of fish are normal because of morphological characteristics, i.e., phenotypic plasticity, new species, cryptic diversity, genotypic variation, or different life stages. In the present study, ambiguous delineation mainly appeared in the taxa or genera Alepes, Acanthopagrus, Johnius, Istiompax, Scomberoides, Rastrelliger, Decapterus, Carangoides, Saurida, Platycephalus, Epinephelus, Uranoscopus, Cynoglossus, Sillago, and Sardinella, and families Apogonidae, Bothidae, Clupeidae, Theraponidae, Trichiuridae, Mugilidae, and Engraulidae, among which misidentifications, cryptic diversity, and new species were common (Mat Jaafar et al, 2012;Qin et al, 2013;Gon et al, 2015;Tucker et al, 2016;Fricke, 2018;Hata and Motomura, 2018;Chao et al, 2019;Frable et al, 2019;Huang et al, 2020;Prokofiev, 2021;Xiao et al, 2021). Developing a reliable DNA barcode library for these taxa, with correct species identifications via morphology, or using multiple DNA fragments is recommended in future studies (Chakraborty et al, 2006;Hsu et al, 2009).…”
Section: Performance Of Molecular Techniques For Identifying Fish Eggsmentioning
confidence: 46%
“…in the northern SCS, and the new species Strophidon tetraporus sp. nov. (Huang et al, 2020). The spawning grounds of these species are not well known, mainly because of difficulties experienced with accurate identification of their eggs and larvae, and lack of any illustrated handbooks.…”
Section: Spawning Periods and Ichthyoplankton Assemblage Structure Off The Pearl River Estuarymentioning
confidence: 99%